Emotional processing through songwriting - Ingunn Huld Sævarsdóttir 1983- (2018)
This reflective report deals with emotional processing through songwriting. It’s a part of my Professional Integration Project that evolves around songs that I wrote during my studies at Iceland University of the Arts, two concerts were the songs were shared and an older song of mine that was recorded and released along with a music video. In this report I go over the methods I used in the songwriting process. Since some of the songs were written as I was emotionally processing a miscarriage I explore the field of therapeutic songwriting as well as songs by other singer-songwriters that I would consider written through emotional processing. I also specifically explore songs about pregnancy and miscarriage by a few female singer-songwriters. I reveal my background and reasons for songwriting and sharing songs and briefly how it connects with the tradition of the singer-songwriter. Some of the songs were written as I was processing positive emotions or as a means to encourage people, so I go through that as well as mentioning how that relates to the term pep-pop. Other songs are written in spontaneous and experimental ways and are also mentioned. The methods I used while writing this report have been exploring the subject in books, on the internet, in music by others as well as in my own work and journals. I also interviewed an Icelandic singer-songwriter that uses emotional processing in songwriting. The physical experience of pregnancy is a nine months reality for many women and it’s interesting why women haven’t written more songs on the subject and allowed themselves to portray a reality that distinguishes them from men. To get information on more songs by Icelandic women on the subject of pregnancy and miscarriage I asked for information in a group on Facebook for female musicians in Iceland. I did not find many songs or lyrics on the topic but this seems to be a subject that sometimes is too personal to be shared or if shared, it’s hidden in poetry and not easy to interpret. I would not be surprised if there ...